Designing a virtual reality programming environment for quantum computers - ERDAL, HASAN; AYDIN, SERKAN (WILEY, 2022)
Quantum computation based on quantum physics is spreading rapidly with many interdisciplinary studies from machine learning to genetics. After the unveiling of real quantum computers, this process has been rising almost exponentially. We are about to experience an effect with quantum computers similar to the effect created by the process from the first electromechanical computers to very large-scale integrated circuit computers. In the programming of quantum computers, we are in a similar place to programming classical computers at an early stage. There are various models in quantum computing, and the most widely used model is quantum gates. Therefore, an easy and practical understanding of the behavior of the gates used in the programming of quantum computers is of great importance. To realize this process, a virtual reality (VR)-based teaching platform of quantum computer programming called QU-VR Education Tool was designed by using Unity 3D VR. In the creation of this design, IBM's so-called Quantum Composer platform and Microsoft Quantum Katas were taken as a reference. In this study, the design process and usage of a novel VR-based platform are presented in detail.
Keywords: quantum composer; quantum computation; quantum gates; Unity 3D; virtual education; virtual reality; SYSTEM